Pembelajaran KPK dan FPB yang Menyenangkan pada Anak-Anak SD GMIT Lamalu - Maktisen Ena; Narita Yuri Adrianingsih (Pemberdayaan Masyarakat : Jurnal Aksi Sosial, 2025)
This community service aims to improve learning outcomes and the process of learning mathematics, especially the Greatest Common Factor (GCF) and the Least Common Multiple (LCM) in Elementary Schools to be more active and enjoyable. Learning LCM and LCM in Elementary School children can be said to have not had much impact because some students do not understand the process of solving LCM and LCM through factor trees and factoring. Community service activities were carried out in one day at SD GMIT Lamalu, Pantar District, Alor Regency. We were present to deliver material about LCM and LCM. During the community service, several students were interested in completing the material or questions given using factor trees. In the learning process about LCM and LCM, it can run well and can improve the quality of learning for students at SD GMIT Lamalu.